Innan döden inträffar: Övervakningsbilder och brottsjournalistik - Carlsson, Eric (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2013)
This article discusses the construction of death in popular media’s use of surveillance footage, and more specifically images depicting the time before death occurs. There are many explanations why these kinds of images of death seem to fit the media format: They are assumed to be authentic, they potentially produces a point of identification for spectators, and finally they represent the time before it is all too late – before death occurs. Hence, they paradoxically represent also hope.